Evaluating a primary care psychology service in Ireland: a survey of stakeholders and psychologists. (8th December 2016) - Corcoran, Mark; Byrne, Michael
Abstract: Primary care psychology services (PCPS) represent an important resource in meeting the various health needs of our communities. This study evaluated the PCPS in a two‐county area within the Republic of Ireland. The objectives were to (i) examine the viewpoints of the service for both psychologists and stakeholders (healthcare professionals only) and (ii) examine the enactment of the stepped care model of service provision. Separate surveys were sent to primary care psychologists ( n  = 8), general practitioners (GPs; n  = 69) and other stakeholders in the two counties. GPs and stakeholders were required to rate the current PCPS. The GP survey specifically examined referrals to the PCPS and service configuration, while the stakeholder survey also requested suggestions for future service provision. Psychologists were required to provide information regarding their workload, time spent on certain tasks and productivity ideas. Referral numbers, waiting lists and waiting times were also obtained. All 8 psychologists, 23 GPs (33% response rate) and 37 stakeholders (unknown response rate) responded. GPs and stakeholders reported access to the PCPS as a primary concern, with waiting times of up to 80 weeks in some areas. Service provision to children and adults was uneven between counties. A stepped care model of service provision was not observed. Access can be improved by further implementation of a stepped care service, developing a high‐throughput service for adults (based on a stepped care model), and employing a single waiting list for each county to ensure equal access.